High-Reliability Organizations: Changing the Culture of Care in Two Medical Units. - Van Stralen, Daved (Design Issues)
The article presents a set of design issues and design ideas that are exceptionally relevant to new forms of design practice, for example, design that involves human interaction, substantive forms of service design, and complex human systems. It presents the design and development of a pediatric intensive care unit and a pediatric nursing home. This account demonstrates how personal experience in a related, but different environment, along with several key theories, can be brought into practice through effective leadership and design thinking.